2013
DOI: 10.1371/journal.pone.0074877
|View full text |Cite
|
Sign up to set email alerts
|

Defluorination of Aqueous Perfluorooctanesulfonate by Activated Persulfate Oxidation

Abstract: Activated persulfate oxidation technologies based on sulfate radicals were first evaluated for defluorination of aqueous perfluorooctanesulfonate (PFOS). The influences of catalytic method, time, pH and K2S2O8 amounts on PFOS defluorination were investigated. The intermediate products during PFOS defluorination were detected by using LC/MS/MS. The results showed that the S2O8 2− had weak effect on the defluorination of PFOS, while the PFOS was oxidatively defluorinated by sulfate radicals in water. The defluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…This observation agrees with data reported in a recent study 27 but is at odds with the results of a study in which PFOS was transformed by heat-activated persulfate to produce shorter-chain PFCAs. 31 It is difficult to reconcile the results of the study in which PFOS degradation was reported for several reasons. First, the temperature at which persulfate activation was performed was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation agrees with data reported in a recent study 27 but is at odds with the results of a study in which PFOS was transformed by heat-activated persulfate to produce shorter-chain PFCAs. 31 It is difficult to reconcile the results of the study in which PFOS degradation was reported for several reasons. First, the temperature at which persulfate activation was performed was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…One research group employed S 2 O 8 2− concentrations of up to 84 mM and activation temperatures up to 60°C, but observed no PFOS defluorination, 27 whereas another research team reported up to 22.5% defluorination of PFOS using 18.5 mM of heat-activated S 2 O 8 2− . 31 …”
Section: Introductionmentioning
confidence: 99%
“…Sulfate radical-based AOPs were also tested for PCB removal and the presence of chloride ion inhibited their transformation (Fang et al, 2012). Persulfate oxidation processes were applied to PFOA using UV-visible light (Hori et al, 2005(Hori et al, , 2008 and PFOS using an UV lamp (Yang et al, 2013). Persulfate produced a highly oxidative sulfate radical anion and PFOA (1.35 mM) was efficiently removed in 4 h (Hori et al, 2005).…”
Section: Miscellaneousmentioning
confidence: 99%
“…Its comparative stability and pH independent activity, makes it reactive with a wide range of pollutants [ 67 ]. It also react with electron-rich moieties via various reaction routes such as hydrogen abstraction, electron exchange and direct oxygen transfer [ 68 ]. Hori et al.…”
Section: Advanced Oxidation Processes For Pfas Degradationmentioning
confidence: 99%